Building virtual communities : learning and change in cyberspace - Renninger, K. Ann; Shumar, Wesley (Learning in doing., 2002)
Building Virtual Communities examines how learning and cognitive change are fostered by online communities. Contributors to this volume explore this question by drawing on their different theoretical backgrounds, methodologies, and personal experience with virtual communities. This book will interest educators, psychologists, sociologists, and researchers in human- computer interaction.